Menopause Is Associated With Immune Activation in Women With HIV. (26th June 2021) - Peters, Brandilyn A; Xue, Xiaonan; Sheira, Lila A; Qi, Qibin; Sharma, Anjali; Santoro, Nanette; Alcaide, Maria L; Ofotokun, Igho; Adimora, Adaora A; McKay, Heather S; Tien, Phyllis C; Michel, Katherine G; et al.
Abstract: Background: Persistent immune activation due to gut barrier dysfunction is a suspected cause of morbidity in HIV, but the impact of menopause on this pathway is unknown. Methods: In 350 women with HIV from the Women's Interagency HIV Study, plasma biomarkers of gut barrier dysfunction (intestinal fatty acid binding protein; IFAB), innate immune activation (soluble CD14 and CD163; sCD14, sCD163), and systemic inflammation (interleukin-6 and tumor necrosis factor receptor 1; IL-6, TNFR1) were measured at 674 person-visits spanning ≤2 years. Results: Menopause (post- vs premenopausal status) was associated with higher plasma sCD14 and sCD163 in linear mixed-effects regression adjusting for age and other covariates (β = 161.89 ng/mL; 95% confidence interval [CI], 18.37–305.41 and 65.48 ng/mL, 95% CI, 6.64–124.33, respectively); but not with plasma IFAB, IL-6, or TNFR1. In piece-wise linear mixed-effects regression of biomarkers on years before/after the final menstrual period, sCD14 increased during the menopausal transition by 250.71 ng/mL per year (95% CI, 16.63–484.79; P = .04), but not in premenopausal or postmenopausal periods. Conclusions: In women with HIV, menopause may increase innate immune activation, but data did not support an influence on the gut barrier or inflammation. Clinical implications of immune activation during menopausal transition warrant further investigation. Abstract : In women living with HIV on antiretroviral therapy, menopause was associated with increased levels of innate immune activation plasma biomarkers soluble CD14 and CD163, but not with biomarkers of gut barrier dysfunction or systemic inflammation.